2022
DOI: 10.1021/jacs.2c01929
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Mapping of Small-Molecule RNA-Binding Sites in Cells Informs an Isoform-Specific Degrader of QSOX1 mRNA

Abstract: The interactions between cellular RNAs in MDA-MB-231 triple negative breast cancer cells and a panel of small molecules appended with a diazirine cross-linking moiety and an alkyne tag were probed transcriptome-wide in live cells. The alkyne tag allows for facile pull-down of cellular RNAs bound by each small molecule, and the enrichment of each RNA target defines the compound’s molecular footprint. Among the 34 chemically diverse small molecules studied, six bound and enriched cellular RNAs. The most highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 34 publications
0
57
0
Order By: Relevance
“…Little is known about the RNA off-target interactions of protein-targeted drugs in vivo, especially for clinically approved drugs. Investigation of small molecule-RNA interactions has been carried out recently via photocrosslinking (diazirine) 7,8 , alkylation (chlorambucil) 9,10 , in-line probing 11 , and SHAPE 12 , and these have emerged as useful tools to identify RNA-ligand interactions in vitro and recently in cultured cells 13 . Although elegant, application of these methods in vivo is potentially limited by transcriptional effects during prolonged probe treatment 14 , cellular damage by ultraviolet irradiation 15,16 , and nucleobase biases [17][18][19] .…”
mentioning
confidence: 99%
“…Little is known about the RNA off-target interactions of protein-targeted drugs in vivo, especially for clinically approved drugs. Investigation of small molecule-RNA interactions has been carried out recently via photocrosslinking (diazirine) 7,8 , alkylation (chlorambucil) 9,10 , in-line probing 11 , and SHAPE 12 , and these have emerged as useful tools to identify RNA-ligand interactions in vitro and recently in cultured cells 13 . Although elegant, application of these methods in vivo is potentially limited by transcriptional effects during prolonged probe treatment 14 , cellular damage by ultraviolet irradiation 15,16 , and nucleobase biases [17][18][19] .…”
mentioning
confidence: 99%
“…Summary of fragment-based ligand identification strategies for RNA. Previously reported methods for identification of fragment binders for RNA, including NMR spectroscopy, mass spectrometry (MS), equilibrium dialysis, Chem-CLIP-Frag-Map, , and SHAPE probing, compared to this work. Representative examples of fragment hits identified from each method and their affinities for the RNA target are provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, here, we have shown that compounds of low molecular weight and, hence fragment-like characteristics, should be considered when identifying bioactive chemical matter that binds RNA, affording mechanistically defined small molecules that selectively affect RNA-mediated pathways. It will be interesting to study whether fragments outside the heterocycle space in particular or the currently known RNA-binding space in general have binding capacity and if these interactions can be detected by the methods established herein or others. Interestingly, some of the fragment hits observed from chemical cross-linking and isolation by pull-down fragment mapping (Chem-CLIP-Frag-Map) suggest that non-heterocyclic compounds also bind RNAs. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations